2018
DOI: 10.3390/cosmetics5010014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ultraviolet Radiation Wavelengths Causing Hardening and Reduced Elasticity of Collagen Gels In Vitro

Abstract: Regular exposure of facial skin to sunlight promotes wrinkle formation; ultraviolet (UV) radiation causes the skin to harden and lose its elasticity. To study UV damage to the skin in vitro, a short-term in vitro photoaging model is required. Hence, the UV transmittance of excised human skin was measured. Changes in elasticity in the cheeks of humans of different ages were investigated. Moreover, changes in the hardness and elasticity of collagen gels following UV exposure were investigated. UV rays penetrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…A xenon light source, Lightning Cure LC6 (150 W xenon lamp L8253; Hamamatsu Photonics K. K.; Hamamatsu, Japan), fitted with a UVC cut filter was used for UV-radiation exposure [19]. The spectrum of this xenon light source in the UV region closely resembled that of solar UV radiation, and the intensity of emission was 25 times greater than that of solar UV radiation [19]. The surface and cross-section of hair not exposed to UV radiation and similarly treated hair exposed to the xenon light source for 20 min were observed.…”
Section: Methods Of Exposure To Uv Radiationmentioning
confidence: 99%
“…A xenon light source, Lightning Cure LC6 (150 W xenon lamp L8253; Hamamatsu Photonics K. K.; Hamamatsu, Japan), fitted with a UVC cut filter was used for UV-radiation exposure [19]. The spectrum of this xenon light source in the UV region closely resembled that of solar UV radiation, and the intensity of emission was 25 times greater than that of solar UV radiation [19]. The surface and cross-section of hair not exposed to UV radiation and similarly treated hair exposed to the xenon light source for 20 min were observed.…”
Section: Methods Of Exposure To Uv Radiationmentioning
confidence: 99%
“…Likewise, Kontomaris et al, showed that UV irradiation caused a significant decline in young's modulus values in collagen fibrils and fibril diameters, length and leads [145]. The above results thus validated the destroyed structural integrity seen in photo-aged human skin, such as dryness, wrinkle formation [146]. Studies have shown that UVA rays exhibit a more substantial effect than UVB rays in destroying collagen, where wavelengths of 300-340 nm caused hardening and reduced elasticity of in-vitro tested collagen gels, with a pronounced effect at 330-nm radiation [147].…”
Section: Collagenesismentioning
confidence: 58%
“…Lightning Cure LC6 (150 W xenon lamp L8253; Hamamatsu Photonics K. K.; Hamamatsu, Japan) lamps were used as the UV source. A long-pass filter with a 280 nm cutoff (A9616-03; Hamamatsu Photonics K. K.; Shizuoka, Japan) was used in these lamps [27,28]. Hair glossiness was examined using a Glossymeter GL20 (Courage+Khazaka Electronic GmbH; Köln, Germany).…”
Section: Equipmentmentioning
confidence: 99%